Preparation and Evaluation of Quality of Fish Burger from Sea Bass (Centropristis striata) - Aberoumand, Ali; Matoori, Abbas; Seyyedi, Sadra (Current Nutrition & Food Science, 2025)
BackgroundFish is considered one of the most important foods around world due to its high nutritional value and good sensory quality, and there are a variety of ways to prepare it.AimThe purpose of the study was to research the effects of additives and different cooking methods on the physicochemical and nutritional properties of fish burgers. This research aimed to prepare fish burgers from sea bass fish fillets treated with a mixture of additives and to evaluate the quality of the produced product and stored at -4°C condition.Materials and MethodsResults were measured using AOAC standard methods: which showed a significant difference between chemical compositions in treated burgers, so that moisture, and protein contents decreased, and fat and ash contents increased. A noticeable increase in energy value, yield, and expressible moisture was recorded for treated fish burgers, but these increases were found within permissible limits. Although there were no significant differences between values of water holding capacity, but a noticeable increase was recorded for weight loss, and this increase was at a lower rate in treated burgers.ConclusionThe different frying methods and additives were being processed. Physical properties were significantly affected by frying, while all products were acceptable until the end of experiment. It is clear that high quality products can be prepared from sea bass fish fillets and can be frozen without affecting their quality standards. This is considered a good start for using sea bass fish in markets of Iran.
Keywords: Sea bass fillet